A combined dislocation - Cohesive zone model for fracture in a confined ductile layer - Broedling, Nils C.; Hartmaier, Alexander; Gao, Huajian (International Journal of Fracture, 2006)
The collective dislocation behavior near a crack tip in a ductile layer sandwiched between two brittle solids is analyzed via two-dimensional dislocation dynamics (DD) simulations that incorporate a cohesive zone (CZ) model. The cohesive crack tip is treated as part of a much larger finite crack confined in the ductile layer. The underlying boundary value problem is formulated with a set of boundary integral equations and numerically evaluated with a collocation method. The fracture energy of the layered composite material is shown to be strongly correlated with the layer thickness and is directly influenced by the cohesive strength of the ductile layer (Hsia KJ et al. (1994) J Mech Phys Solids 6 877-896). © Springer Science+Business Media B.V. 2006.
Created from Fastlane, Scopus look-up
Keywords: Confinement effects; Constrained plasticity; Discrete dislocation dynamics; Layered material; Microscale plasticity; Thin films